Öffentliche Räume in Pompeji Zum Design urbaner Atmosphären - Haug, Annette (Decorative Principles in Late Republican and Early Imperial Italy (Decor), 2023)
Experiencing towns means feeling atmospheres. This impact made by urban spaces depends largely on their architecture and its decorative and visual features - including its design. In this sense, this volume is about aesthetic, semantic, and functional design strategies in ancient Pompeii and the impact they had on urban actors.